New bio- and chemostratigraphic data from southwestern China and its relation to Telychian (Llandovery, Silurian) climate change - Yan, Guanzhou; Lehnert, Oliver; Männik, Peep; Calner, Mikael; Li, Lixia; Wei, Xin; Gong, Fangyi; Luan, Xiaocong; Wu, Rongchang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)
Integrated conodont and carbon isotope data is presented from the Telychian (upper Llandovery, lower Silurian) from the Baicaoping section, Yunnan Province, southwestern China. Three conodont zonal units, in stratigraphically ascending order, the Pterospathodus eopennatus Superzone, Pterospathodus celloni Superzone, and the Pterospathodus amorphognathoides amorphognathoides Zone, are recognized in the Baizitian Formation. The new high-resolution carbon isotope data, combined with the conodont biostratigraphy, reveal a continuous Valgu carbon isotope excursion (Valgu CIE) in the Pt. eopennatus Superzone and the Manitowoc carbon isotope excursion (Manitowoc CIE) in the Pt. celloni Superzone. Because of this, the studied section in the Baizitian Formation can be precisely correlated with corresponding sections in Baltica (Viki core section in Estonia) and Laurentia (Composite Jupiter-Chicotte section on Anticosti Island, Canada; Sheboygan 541 section, Michigan Basin, USA), based on biostratigraphy and the comparable shape of the carbon isotope curves. The Manitowoc CIE constitutes a relatively minor positive anomaly in the upper Baizitian Formation (middle Telychian), reflecting a widely identifiable perturbation of the carbon cycle during the Manitowoc Icehouse interval. Our high-resolution δ13Ccarb record improves the Telychian bio- and chemostratigraphic framework and refines global correlations and comparisons between Silurian successions in South China, Baltica, and Laurentia.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Conodont biostratigraphy; Manitowoc CIE; Telychian climate change; Valgu CIE